A success case method evaluation of a school-based HIV/AIDS programme by life orientation teachers in Sedibeng West secondary schools [gde] - Mbada, Ndavheleseni Albert (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.